Dynamic Visual Abstraction of Soccer Movement - Sacha, D.; Al‐Masoudi, F.; Stein, M.; Schreck, T.; Keim, D. A.; Andrienko, G.; Janetzko, H. (Computer graphics forum, 2017)
Trajectory‐based visualization of coordinated movement data within a bounded area, such as player and ball movement within a soccer pitch, can easily result in visual crossings, overplotting, and clutter. Trajectory ion can help to cope with these issues, but it is a challenging problem to select the right level of ion (LoA) for a given data set and analysis task. We present a novel dynamic approach that combines trajectory simplification and clustering techniques with the goal to support interpretation and understanding of movement patterns. Our technique provides smooth transitions between different ion types that can be computed dynamically and on‐the‐fly. This enables the analyst to effectively navigate and explore the space of possible ions in large trajectory data sets. Additionally, we provide a proof of concept for supporting the analyst in determining the LoA semi‐automatically with a recommender system. Our approach is illustrated and evaluated by case studies, quantitative measures, and expert feedback. We further demonstrate that it allows analysts to solve a variety of analysis tasks in the domain of soccer.